Trabalho feminino precarizado, sexismo e violência de gênero: uma avaliação em profundidade da política de fiscalização urbana de Fortaleza - Mascarenhas, Muniky Crisóstomo Chaves Pequeno (2022)
The general objective of this dissertation is to evaluate the inspection policy of the Inspection Agency of the city of Fortaleza (AGEFIS), focusing on understanding how precarious female work, sexism and gender violence impact the bonds of women inspectors with their work. The premise is that the historical alignment between capitalism and the patriarchal system produces gender inequalities in the workplace. AGEFIS is taken as an empirical field, seeking, through the Depth Assessment approach (RODRIGUES, 2008), to understand the meanings and meanings that the inspection policy has for the inspectors who carry it out. With such an evaluation proposal, the aim is to carry out an analysis under multiple dimensions, examining the context of its implementation, its content and temporal/territorial spectrum. The research has a qualitative nature and data collection was carried out through participant observation, the analysis of documents and semi-structured interviews with 13 inspectors, divided between the groups of managers, internal and field of the Inspection Agency. The reports collected through the interviews were submitted to content analysis and showed that precarious working conditions, violence, sexism and motherhood are the main obstacles that intensify gender asymmetries in the work of inspection, generating feelings of fear, insecurity, lack of motivation and fragility in their professional identities. In addition, it was evidenced that the inspectors feel useful with the work in the inspection policy, but that the creation of AGEFIS arouses feelings of frustration and exclusion in the internal and field inspectors, unlike the managing inspectors, who feel supported and valued. Thus, with the aim of contributing to the improvement of the formulation of inspection policies, qualitative indicators were also proposed so that the knowledge generated collaborates with the promotion of gender equality in labor relations.